2020
DOI: 10.3389/fcimb.2020.580371
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR Genome Editing Applied to the Pathogenic Retrovirus HTLV-1

Abstract: CRISPR editing of retroviral proviruses has been limited to HIV-1. We propose human T-cell leukemia virus type 1 (HTLV-1) as an excellent model to advance CRISPR/Cas9 genome editing technologies against actively expressing and latent retroviral proviruses. HTLV-1 is a tumorigenic human retrovirus responsible for the development of both leukemia/lymphoma (ATL) and a neurological disease (HAM/TSP). The virus immortalizes and persists in CD4+ T lymphocytes that survive for the lifetime of the host. The most impor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 82 publications
0
9
0
Order By: Relevance
“…A multitude of other oncogenic viruses have been described and treated using CRISPR/Cas9 gene editing including: Epstein-Barr virus (EBV) causing nasopharyngeal cancer, Burkitt’s lymphoma or Hodgkin’s lymphoma [ 96 , 97 ]; Hepatitis B and C viruses (HBV and HCV respectively) in hepatocellular carcinoma [ 98 , 99 , 100 ] and Human herpesvirus 8 (HHV-8) causing Kaposi’s sarcoma [ 101 , 102 ]. Many more neoplasms caused by oncogenic viral infections still await targeted genetic therapy, for example an adult T-cell leukemia/lymphoma induced by Human T- cell leukemia virus type 1 (HTLV-1) infection [ 103 ], or Merkel cell carcinoma - an aggressive skin cancer caused by Merkel cell polyomavirus (MCV) [ 104 ].…”
Section: Targeted Modification Of Cancer-specific Sequencesmentioning
confidence: 99%
“…A multitude of other oncogenic viruses have been described and treated using CRISPR/Cas9 gene editing including: Epstein-Barr virus (EBV) causing nasopharyngeal cancer, Burkitt’s lymphoma or Hodgkin’s lymphoma [ 96 , 97 ]; Hepatitis B and C viruses (HBV and HCV respectively) in hepatocellular carcinoma [ 98 , 99 , 100 ] and Human herpesvirus 8 (HHV-8) causing Kaposi’s sarcoma [ 101 , 102 ]. Many more neoplasms caused by oncogenic viral infections still await targeted genetic therapy, for example an adult T-cell leukemia/lymphoma induced by Human T- cell leukemia virus type 1 (HTLV-1) infection [ 103 ], or Merkel cell carcinoma - an aggressive skin cancer caused by Merkel cell polyomavirus (MCV) [ 104 ].…”
Section: Targeted Modification Of Cancer-specific Sequencesmentioning
confidence: 99%
“…Currently, clinical studies addressing the impact of ART on the PVL in breast milk of HTLV-1-infected mothers or, vice versa, assessing the use of prophylactic treatment of the suckling, using for example integrase inhibitors, are lacking but might serve as a promising and cost-effective tool to prevent MTCT. Future challenging strategies to get rid of the integrated virus within infected mothers could include excision strategies using HTLV-1-specific recombinases that have already been evolved for HIV ( 96 , 97 ), zinc finger nucleases ( 98 ) or genetic editing strategies using CRISPR/Cas 9 ( 99 ). Hence, it may be easier to prevent de novo infection of the infant.…”
Section: How To Inhibit Oral Htlv-1 Transmission Despite Breastfeedin...mentioning
confidence: 99%
“…Regarding the application of new therapeutic technologies, much discussion has been raised surrounding the use of CRISPR (Clustered Regularly Interspaced Short Palindromic Repeats) for antiretroviral therapy (Panfil et al, 2020). Prior to the use of CRISPR systems, zinc finger nucleases (ZFNs) targeting LTR promoters were utilized to inhibit the proliferation of HTLV-1 infected cell lines (Tanaka et al, 2013).…”
Section: Antisense Transcription Models In Retroviral Therapeuticsmentioning
confidence: 99%
“…In this methodology published in 2013, the therapeutic effects of HTLV-1 elimination were supported in vivo, and it was further suggested that zinc finger nucleases could be used to remove HTLV-1 proviral genomes from infected cells for therapeutic benefit (Tanaka et al, 2013). However, with the onset of wider application of CRISPR technologies, multiple factors suggest that CRISPR may be a more optimized alternative to ZFN-based therapies, including greater cost-effectiveness, simplicity, and efficiency (Panfil et al, 2020). Even greater support lies in that such implementation has already been shown to effectively decrease ATLL cell proliferation in vitro (Nakagawa et al, 2018).…”
Section: Antisense Transcription Models In Retroviral Therapeuticsmentioning
confidence: 99%